Cadeia de suprimentos verde: uma análise sobre um programa de logística reversa para destinação final de embalagens recicláveis - Martins, Gislene Aparecida de Moura (2014)
New demands of international and national markets are pressuring organizations and especially to industries in pursuit of sustainable development. The adoption of environmental management in the green supply chain is one. Moreover, reverse logistics programs, shared responsibility among the participants of the chain and proper disposal are also important points and have also been discussed by contemporary society. In this sense, there is a gap that led to the deepening of this academic study that aimed to examine the operation of a reverse logistics program, which aims to contribute to the mitigation of environmental impacts, for collecting recyclable packaging in a household appliance manufacturer, leading Marketplace. Therefore, a literature review that focused on green supply chain, reverse logistics, management of solid waste and recyclable packaging was performed. The qualitative research is exploratory and was developed from analysis of documents, files, indirect observation and semi - structured interviews. One single case study was conducted at the manufacturer Whirlpool. The results of this research show that environmental practices and environmental management are current issues within organizations. This study also recognizes the environmental approach, taking into consideration, proactive and adding value in business environment reactive aspects. Were evidenced in this reverse logistics recyclable packaging program, called Program Brastemp Viva! proactive and adding value with the use of environmental criteria adopted by the company researched aspects . It was also noted that there is influence of the company object of study for environmental practices in relation to partners directly involved in the program and are part of the reverse chain , taking into account that this program was created in 2003 , seven years before the implementation of PNRS 2010 . The Program Brastemp Viva! through reuse of packaging and, later sending waste from recyclable packaging (packaging unusable) for recycling , serves two basic with regard to the principles of 4Rs and environmental indicators GRI requirements and Ethos . The GCSV can contribute in improving the environmental performance of an organization and provide them the opportunity to exceed the environmental expectations of governments and customers through collaboration in green supply chain. The initiative the Program Brastemp Viva! can serve as a model for other independent organizations operating segment.